Online Activism of Social Community in Handling Social Issues in The City Of Malang - Tia Subekti; Irza Khurun'in (Pascasarjana Universitas Jenderal Soedirman, 2020)
his paper aims to see the formation of social movements in Malang addressing social issues in Malang. Some of the movements that become the focus of this paper are the Malang Care Community or ASLI Malang and Social and Humanist Society in Malang. Interestingly, the communities are doing their activities online and using social media as the main instrument of movement. If in general online media based-communities are only informative, it is different with Malang. Here the communities perform real actions such as social activities. For examples: social aids for victims of natural disasters, street children, poor people who need help, and other problems. Last but not least is the emergence of free motorcycle-taxi riders that arose due to the protest of angkot (city transport) drivers toward online motorcycle taxi resulting in an angkot drivers’ strike. The movement was able to collect motorcycle-rider volunteers up to 700 motorcycles and 80 cars. The 4 days activity was the culmination of the social community awakening which arises in response to socio-dynamic in society The emergence of various social communities is the marker of the rise of civilian powers and the strengthening of non-state actors. The social community as a form of movement becomes an alternative for civil society to engage in social issues, rather than to join political organizations such as political parties or interest groups whose main interests are political interests. Charles Tilly (2004) defines social movements as an organized public collective effort to make certain claims to the intended authorities. Sidney Tarrow (2004) explains that social movements are generally born from social problems that lead to contentious. The orientation of social movements is to create a world order of social justice. Furthermore, in data collection, the authors conducted in-depth interviews, observations, and documentation. By using social movement perspective, the main argument in this paper is, first, social media is the social community's main strategy for activism. Second, the pattern of social movements that arise is departing from social concerns of civil society in the city of Malang in view of social issues. Third, the formation of activism conducted by the social community in the City of Malang City aims to respond to social problem